Psychological and social stressors and psychiatric comorbidity in patients with migraine without aura from headache centers in Italy: a comparison with tension-type headache patients - Puca, Francomichele (Springer-Verlag Italia, 2000)
A multicenter study was carried out to investigate the prevalence of psychosocial stressors and psychiatric comorbidity in patients suffering from migraine without aura (MWO) according to the International Headache Society criteria. Two hundred four adult MWO outpatients underwent a structured psychiatric interview (CIDI-c) to determine the presence of anxiety, and mood and somatoform disorders according to DSM-III-R criteria. An ad hoc questionnaire was used to assess psychosocial stress events. Anxiety disorders were found in 39.2% of the sample, mood disorders occurred in 23.0% and somatoform disorders in 21.6%. Psychosocial stressors were identified in 22.5% of the migraineurs without any difference between patients with and without psychiatric comorbidity. No correlation was found between psychiatric comorbidity and migraine duration or frequency. When the migraine patients were compared with a homogeneous group of tension-type headache sufferers, a higher frequency of psychiatric comorbidity was found in the latter group (56.4% vs. 77.8%, p = 0.01). These data suggest that migraine as well as tension-type headache are associated with an increased vulnerability to psychiatric disorders. Whether this is related to a common genetic susceptibility or is the effect of a psychoneurobiological loop related to the stress response activation remains to be investigated.